Exploring the Impact of Social Media Platforms on the Communication of Traditional Performing Arts Based on the Protection of Cultural - Xiao, Yuhan (Transactions on Social Science, Education and Humanities Research, 2025)
In the context of digitalisation and globalisation, traditional performing arts are facing multiple crises such as succession gap, limited dissemination and loss of audience. Through algorithmic recommendation and user co-creation mechanism, social media platforms have provided a new path for digital ‘broken circle’ communication, but also triggered the controversy of deep cultural dilution and commercial alienation. Taking the explosion of popularity on the social media platform of the environmental-style Yue opera The New Dragon Gate Inn and the digital communication innovation of the classic drama Teahouse as case studies, this paper systematically deconstructs the deeper impact of social media platforms on the communication of traditional performing arts by combining Henry Jenkins’ theory of participatory culture, mediatisation theory, Elihu Katz’s use and gratifications theory, and Theodor Adorno’s critical theory of cultural commodification. The study found that the logic of mediatisation erodes the ontology of art while providing technological innovations, participatory culture poses the risk of a hierarchical division of communication and entertainment, and the commoditisation of culture needs to set a value floor to preserve artistic depth.